A DFT Study of Strecker Intermediates as Scavengers for Cyanides - Flores-Sandoval, C.A.; Godinez-Salomon, F.; Hallen-Lopez, J.M.; Beltran, H.I.; Hernandez-Altamirano, R.; Nieto-Alvarez, D.A.; Zamudio-Rivera, L.S. (Asian Journal of Chemistry, 2012)
Bis-(aminomethyl)ethers (1-4) have been employed as molecular scavengers for cyanides. They are theoretically studied herein at DFT, thus enabling a theoretical study in order to elucidate why the efficiency as scavenger depends on the substituent placed at the nitrogen atom. The local softness (s+) value for C2 from electrostatic potential analysis (ESP) shows that the following decreasing order of reactivity is in accordance with the experimental yield values: 4, 1, 2 and 3. 1290 runs considering four to ten parameters such as N3-C2 and C2-O1 bond lengths, HOMO and LUMO energies, GAP, dipolar moment, partition coefficient, atomic charge, local softness, global hardness, electronegativity and 13C NMR chemical shift were taken into account in a structure-activity relationship study. In particular five runs of linear combination of four (run 259), five (run 517), seven (runs 937 and 1063) and eight (run 1214) molecular indexes have shown the best F values, being the run 517, which present the highest F value 4 to 10 parameters.